1999
DOI: 10.1016/s0029-7844(98)00490-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of persistence of adnexal masses in pregnancy

Abstract: Most adnexal masses identified by sonography during pregnancy were small, simple cysts that did not pose a risk to the pregnancy. Even the majority of large or sonographically complex masses resolved. The best predictors of persistence of the masses were sonographic appearance and size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 20 publications
0
45
0
7
Order By: Relevance
“…Similarly, the timing of detection of the adnexal mass during pregnancy influences the likely etiology of the mass. Cystic adnexal masses less than 5 cm that are detected in the first 16 weeks are usually functional and almost always resolve spontaneously (2). Ovarian tumors that persist beyond 16 weeks are more likely to be neoplastic; and, therefore, are more likely to result in surgical intervention.…”
Section: Etiologymentioning
confidence: 99%
“…Similarly, the timing of detection of the adnexal mass during pregnancy influences the likely etiology of the mass. Cystic adnexal masses less than 5 cm that are detected in the first 16 weeks are usually functional and almost always resolve spontaneously (2). Ovarian tumors that persist beyond 16 weeks are more likely to be neoplastic; and, therefore, are more likely to result in surgical intervention.…”
Section: Etiologymentioning
confidence: 99%
“…The best predictors of persistence of a mass are complex appearance and size [5 cm [13]. We found that only 13.0 % of adnexal masses \5 cm persisted and were managed surgically as opposed to 60.7 % of those C5 cm.…”
Section: Discussionmentioning
confidence: 74%
“…Conservative management for most masses less than 5 cm is acceptable and spontaneous resolution can be anticipated; however, larger masses have an increased risk of torsion [1]. Thus, resection is generally performed for larger cysts [1][2][3]. Masses between 5 and 10 cm are more difficult to manage.…”
Section: Discussionmentioning
confidence: 99%